2007
DOI: 10.1111/j.1537-2995.2007.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of 200 cases of fetomaternal alloimmune thrombocytopenia

Abstract: HPA-1a antibodies are most commonly implicated in severe thrombocytopenia but HPA-5b and HPA-15b antibodies can also result in poor outcome. Postnatal transfusion management is extremely variable, and fetal transfusions are associated with significant morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
3
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 48 publications
4
146
3
12
Order By: Relevance
“…Either purified polyclonal human anti-HPA 1a immunoglobulin G or recombinant human HPA 1a antibodies could be used for this purpose. 27 We and others have previously reported that anti-HPA 1a antibody levels decrease throughout pregnancy in women who have had a previous pregnancy. 9,[28][29][30] The fact that the levels of antibodies to the rubella antigen were stable during pregnancy disproves the hypothesis that the decrease in anti-HPA 1a antibody levels could be due to the normal hemodilution that occurs during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Either purified polyclonal human anti-HPA 1a immunoglobulin G or recombinant human HPA 1a antibodies could be used for this purpose. 27 We and others have previously reported that anti-HPA 1a antibody levels decrease throughout pregnancy in women who have had a previous pregnancy. 9,[28][29][30] The fact that the levels of antibodies to the rubella antigen were stable during pregnancy disproves the hypothesis that the decrease in anti-HPA 1a antibody levels could be due to the normal hemodilution that occurs during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…FMAIT results from transplacental transfer of maternal antibodies that develop in response to alloimmunization against paternal human platelet antigens (HPAs) expressed on fetal platelets. The HPA-1a antigen is responsible for the great majority of cases of severe FMAIT in individuals of mixed European descent (23). FMAIT is uncommon (affecting approximately 1 in 1,000 births), but it is the most important cause of severe fetal/neonatal thrombocytopenia and is associated with substantial morbidity and mortality due to intracranial hemorrhage, the risk of which is higher if a previous sibling was similarly affected (24).…”
Section: Fc-fcr Interactions In Neonatal Alloimmune Thrombocytopeniamentioning
confidence: 99%
“…The incidence of FNIT has been estimated at 0.5-1.5 per 1,000 liveborn neonates (1)(2)(3)(4). This number, however, does not include miscarriages caused by the disease, since the rate of fetal mortality in affected pregnant women has not been adequately studied, although miscarriage has been reported by several groups (9)(10)(11)(12)(13). Currently, the mechanisms leading to miscarriage in these women and the therapies to prevent this devastating consequence are unknown.…”
Section: Introductionmentioning
confidence: 99%